(untitled) (Modern Problems of Metallurgy, 2020)
Methods for the removal of non-metallic inclusions from steel at various stages of its production are considered: in a teeming ladle, a tundish and a CCM mold. It is proposed to classify methods of non-metallic inclusions removal into two groups: mechanical (inert gas blowing, application of electromagnetic stirrers, etc.) and physical and chemical (modification of non-metallic inclusions, slag treatment, rational deoxidation modes). Particular attention is paid to methods aimed at creating a vortex in the metal, inside which non-metallic inclusions are transported to its axis. The aim of the work is to determine the efficiency of use centrifugal forces to remove non-metallic inclusions at different stages of steel production. To assess the centrifugal force effectiveness, it has been analyzed the transfer time of non-metallic inclusions of various sizes to the vortex axis in the teeming ladle of 50 tons capacity, a rotary chamber of tundish (chamber capacity is 2.0 tons) and the CCM mold of 160 mm in diameter. For typical angular velocities being observed during electromagnetic stirring, the values of the metal inertia moment and the kinetic energy of its rotational motion have been calculated. According to the calculations, the smallest transfer time of inclusions is achieved in the teeming ladle. However, vortex creation in it requires a significant energy. The use of centrifugal force in the mold, although it does not require such a high energy, is also not efficient enough due to the low angular velocity of the vortex, limited by a risk of violating the crust formation in the mold. The possibility of using the kinetic energy of the jet flowing from the teeming ladle to the rotary chamber of the tundish has been assessed.